1980
DOI: 10.1093/ajcn/33.2.244
|View full text |Cite
|
Sign up to set email alerts
|

A study of malabsorption in intestinal tuberculosis: stagnant loop syndrome

Abstract: A study was carried out in the patients with intestinal tuberculosis and obstruction requiring surgery to determine the pathogenesis of malabsorption in this condition. Fifteen of the 20 patients studied had malabsorption, nine of 17 (53%) had intestinal bacterial overgrowth and 10 of 16 (62.6%) had free bile acids in their jejunal aspirates. In a comparable group of nontuberculus intestinal obstruction requiring surgery, six of seven (85.7%) had malabsorption, and four of five (80%) had both the bacterial ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In the study of RK Tandon, biochemical evidence of malabsorption was reported in 75% of patients with intestinal obstruction and in 40% of those without it. 16 The cause of malabsorption in intestinal tuberculosis is postulated to be bacterial overgrowth in a stagnant loop, bile salt deconjugation, diminished absorptive surface due to ulceration, and involvement of lymphatic and lymph nodes. The duration of sickness in the study population before hospital admission ranged from 4 days to 2 years, with mean of 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of RK Tandon, biochemical evidence of malabsorption was reported in 75% of patients with intestinal obstruction and in 40% of those without it. 16 The cause of malabsorption in intestinal tuberculosis is postulated to be bacterial overgrowth in a stagnant loop, bile salt deconjugation, diminished absorptive surface due to ulceration, and involvement of lymphatic and lymph nodes. The duration of sickness in the study population before hospital admission ranged from 4 days to 2 years, with mean of 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical evidence of malabsorption can be found in many patients with intestinal tuberculosis, even though the patient may not present with a clinical diagnosis of the malabsorption syndrome. In one study, biochemical evidence of malabsorption was found in 75% of patients with intestinal tuberculosis with intestinal obstruction, but in only 40% of patients 45 The causes of malabsorption include bacterial overgrowth in a stagnant loop, bile salt deconjugation and diminished absorptive surface due to ulceration and lymphatic obstruction. 46 Considerable abdominal pain in a patient with malabsorption syndrome should alert the clinician to the diagnosis.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…malabsorption of nutrients and/or decreased intestinal transit time. 29 Third, CRP levels may be elevated in both pulmonary and extra-pulmonary active TB. 30,31 A small study on TB-diseased children found an inverse relationship between CRP and body mass index and between leptin levels and CRP, with poorer prognosis in patients with the highest CRP levels.…”
Section: Discussionmentioning
confidence: 99%